2016
DOI: 10.1016/j.copbio.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Combining microbial production with chemical upgrading

Abstract: This review presents developments in the chemical processing of fermentation-derived compounds, focusing on ethanol, lactic acid, 2,3-butanediol and the acetone-butanol-ethanol mixture. We examine pathways from these products to biologically-derived drop-in fuels, polymers, as well as commodity chemicals, highlighting the role of homogeneous and heterogeneous catalysts in the development of green processes for the production of fuels and high-value-added compounds from biomass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Recent investigations of ABE (acetone–butanol–ethanol) fermentation of glucose using clostridium acetobutylicum have shown that a mixture of butanol, acetone, and ethanol can be produced with the molar ratio of 6:3:1 . These products can be further upgraded to afford higher carbon number alcohols and ketones, such as 2‐pentanone, 2‐heptanone, 4‐heptanone, 6‐undecanone, and methyl isobutyl ketone (MIBK) . Some of these compounds can also be prepared from furfural and 5‐hydroxymethyl furfural (HMF) by the dehydration of xylose and glucose, respectively …”
Section: Platform Molecules From Biomass‐derived Feedstocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations of ABE (acetone–butanol–ethanol) fermentation of glucose using clostridium acetobutylicum have shown that a mixture of butanol, acetone, and ethanol can be produced with the molar ratio of 6:3:1 . These products can be further upgraded to afford higher carbon number alcohols and ketones, such as 2‐pentanone, 2‐heptanone, 4‐heptanone, 6‐undecanone, and methyl isobutyl ketone (MIBK) . Some of these compounds can also be prepared from furfural and 5‐hydroxymethyl furfural (HMF) by the dehydration of xylose and glucose, respectively …”
Section: Platform Molecules From Biomass‐derived Feedstocksmentioning
confidence: 99%
“…[71,72] These products can be furtheru pgraded to afford higherc arbon number alcohols and ketones, such as 2-pentanone, 2-heptanone, 4heptanone, 6-undecanone, and methyl isobutyl ketone (MIBK). [7,73,74] Someo ft hese compounds can also be prepared from furfural and 5-hydroxymethyl furfural (HMF) by the dehydration of xylose and glucose, respectively. [75][76][77] Condensation of furfural with acetone in the presence of hydrogen produces 1-octanol.…”
Section: Platform Molecules From Biomass-derived Feedstocksmentioning
confidence: 99%
“…Acetalization involves the formation of acetals (or ketals) from an alcohol or orthoester with carbonyl compounds (e.g., ketones or aldehydes) in the presence of an acid catalyst. Decades of work has shown that glycerol, obtained from hydrolysis of fats, reacts with carbonyl compounds to produce mixtures of cyclic acetals consisting of six-membered ( [1,3]dioxin-5-ols) and five-membered ( [1,3]dioxolan-4-ylmethanols) rings. 41 Such glycerol-derived cyclic acetals are valuable chemicals that can be used as additives for diesel fuels and as building blocks for surfactants.…”
Section: Acetalizationmentioning
confidence: 99%
“…Similarly, a plethora of possibilities are available through heterogeneous and homogeneous chemocatalysis, including reactions of sugars and even complex lignocellulosic materials to yield mixtures of platform chemicals. 2 An alternative strategy 3 leverages both biology and chemocatalysis by deploying biotechnology (fermentations) to produce platform chemicals that are chemically transformed into fuels and other high-value chemicals. 4 While a host of different reactions have been used for biomass upgrading, condensation reactions, such as aldol condensation, etherification, ketonization, and esterification, are particularly significant chemical transformations, because they allow for the upgrading of bio-derived feedstocks…”
Section: Introductionmentioning
confidence: 99%
“…Plant biomass is the most abundant and available source of renewable energy. Utilization of pretreated plant biomass for production of industrially important chemicals such as ethanol, n ‐butanol, lactic acid, 2,3‐butanediol and intermediates for synthetic rubber is the current focus of many research labs around the world …”
Section: Figurementioning
confidence: 99%